Sustaining Customer Growth In Household High Speed Broadband (Hsbb): A Case Of Unifi - Yun, Soon; Goh, Lee San; Razi, Nur Arifi Ahmad (2014)
This paper is to identify the root causes that lead to the decrease of growth rate of Unifi from 104% in 2012 to 30% in 2013. There are eight causes contribute to the issue, specifically TM does not have 4G LTE license to operate wireless High Speed Broadband, TM considers its social obligation to provide service to unprofitable areas, new competitors are serving 20-30 Mbps ahead of TM fixed Unifi offered package, less competitive pricing, constraints in coverage expansion where many places are not Unifi ready, unfavorable promotional strategy, limited package offering and slow response to customer complaints. In order to analyse the case, structured interviews and survey are being conducted; SVP framework is used to identify the problem and solutions.